EFFECT OF DAY OLD CHICKS WEIGHT ON PRODUCTIVE PERFORMANCE OF TWO BROILER STRAINS AND THEIR CROSSING - AL-Shamire, J. S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experment was conducted at the Poultry Farm،Animal production Dept./College of Agriculture. University of Baghdad from 1-4-2014 to 12-5-2014. to investigate the potential effect of day old chicks weight produced from two broiler strains and their crossing  Ross 308 , Arbor Acres and Ross 308 x Arbor Acres on productive performance . A total of 360 day all chicks were distributed randomly to 6 groups with 4 replicate pens )15 birds / pens). The experimental groups were: T1= Ar-medium; T2= Ar - Large ; T3= R-medium; T4= R -Large; T5= R - Arb-medium; T6= R - Ar-Large. Results showed that body weight, weekly average gain, feed conversion ratio, dressing percentage and relative breast weight in female were  significantly (p